If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 2) = 2(x + -13) Reorder the terms: 5(2 + x) = 2(x + -13) (2 * 5 + x * 5) = 2(x + -13) (10 + 5x) = 2(x + -13) Reorder the terms: 10 + 5x = 2(-13 + x) 10 + 5x = (-13 * 2 + x * 2) 10 + 5x = (-26 + 2x) Solving 10 + 5x = -26 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 10 + 5x + -2x = -26 + 2x + -2x Combine like terms: 5x + -2x = 3x 10 + 3x = -26 + 2x + -2x Combine like terms: 2x + -2x = 0 10 + 3x = -26 + 0 10 + 3x = -26 Add '-10' to each side of the equation. 10 + -10 + 3x = -26 + -10 Combine like terms: 10 + -10 = 0 0 + 3x = -26 + -10 3x = -26 + -10 Combine like terms: -26 + -10 = -36 3x = -36 Divide each side by '3'. x = -12 Simplifying x = -12
| 65-7x=38x+15 | | 5x-6(4+5x)=-6 | | x^3-18x^2+17x=0 | | 5-9x=49-37x | | x(x+7)=x^2 | | 54-7x=2x+24 | | 2x+12x-14-108=24x+30 | | -6(-4)(-7)= | | 7-10x=67-45x | | Q=3000-10p | | 5x+2x=2x-4 | | -x^2+5x+14=0 | | 18-2x=6-10x | | 8n+3=67 | | 8x-17=5x+11 | | -2(6)(1)(-4)= | | 71-6x=8+15 | | 2x+6=-24 | | 4-3x=7x+1 | | 10x-118=6x-14 | | (n-4)*7=56 | | (n-7)*2=8 | | -2(n-1)-4n= | | 105-3x=33x+17 | | 7-10x=20-17x | | 2x+31=9x-32 | | 3x+7=-113-9x | | 12x-3=10+5 | | 141-6x=4x+11 | | 2x+12x-14-12=24x+30 | | 137-6x=6x+5 | | 5x+24=13x-72 |